A kind of high activity graphite felt for vanadium battery and preparation method thereof
By using a multi-layer grading structure and organic material skeleton-organic material skeleton structure on the graphite of the battery electrode material.
Patent Information
- Application Number
- CN202411319648.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing vanadium battery electrode material graphite felt exhibits poor electrochemical activity, resulting in poor electrochemical performance of vanadium batteries.
A graphite felt electrode with a multi-layer hierarchical structure is used to polymerize and modify the graphite felt through cyclic voltammetry, and a molybdenum source and an organic phosphine source are added during hydrothermal treatment and heat treatment to form an organic skeleton-metal oxide-organic skeleton structure.
The specific surface area and active sites of the graphite felt are enhanced, the electrochemical performance of the battery is improved, the catalytic effect on the vanadium ion redox reaction is enhanced, and the molybdenum source is protected during long-term use.
Smart Images

Figure CN118867276B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of all-vanadium liquid flow battery electrodes, and in particular to a highly active graphite felt for a vanadium battery and a preparation method thereof. Background Art
[0002] The performance of the electrode, as the site of vanadium redox reaction, directly affects the performance of vanadium batteries. The basic conditions required for ideal electrode materials for vanadium batteries are uniform pore size, large surface area, high activity, good hydrophilicity, structural diversity and stability in acidic environments. Graphite felt, as the electrode material widely used in vanadium batteries, usually exhibits poor electrochemical activity, resulting in poor electrochemical performance of vanadium batteries.
[0003] In view of this, we proposed a multi-layer hierarchical graphite felt electrode and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a high-activity graphite felt for vanadium battery and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0005] The present invention provides the following technical solutions:
[0006] A method for preparing highly active graphite felt for vanadium batteries comprises the following steps:
[0007] Step S1: Mixing an organic sulfur source with dilute sulfuric acid as an electrolyte, using graphite felt as a working electrode, a platinum sheet as an auxiliary electrode, and a silver chloride electrode as a reference electrode to polymerize using cyclic voltammetry to obtain modified graphite felt;
[0008] Step S2: mixing a molybdenum source and deionized water to obtain a molybdenum source solution, adding ammonia water to adjust the pH to 9-10, adding modified graphite felt, and then transferring to a hydrothermal kettle for hydrothermal treatment. After the treatment, taking out the graphite felt, washing and drying it to obtain metal-loaded graphite felt;
[0009] Step S3: mixing an organic phosphine source and deionized water to obtain an organic phosphine source solution, and immersing the metal-loaded graphite felt in the organic phosphine source solution to obtain a precursor graphite felt;
[0010] Step S4: heat-treating the precursor graphite felt in a nitrogen atmosphere to obtain a highly active graphite felt.
[0011] Preferably, the solubility of dilute sulfuric acid in step S1 is 1 mol / L.
[0012] Preferably, in step S1, the organic sulfur source is one of thiophene, 3-methylthiophene, 3-chlorothiophene, and 3-bromothiophene; and the volume ratio of the organic sulfur source to dilute sulfuric acid is 3:20.
[0013] Preferably, in step S1, the voltage window of the cyclic voltammetry is 0-1 V, the scan rate is 10 mV / s, and the number of cycles is 50 times.
[0014] Preferably, in step S2, the molybdenum source is one of sodium molybdate, ammonium molybdate and molybdenum acetate, and the mass fraction of the molybdenum source in the molybdenum source solution is 5-10%.
[0015] Preferably, the hydrothermal treatment temperature in step S2 is 120-180° C., and the time is 8-24 hours.
[0016] Preferably, in step S3, the organic phosphine source is one of phytic acid, aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and diethylenetriaminepentamethylenephosphonic acid, and the mass fraction of the organic phosphine source in the organic phosphine source solution is 10-20%.
[0017] Preferably, the immersion time in step S3 is 8-24 hours.
[0018] Preferably, the heat treatment conditions in step S4 are: a heating rate of 2-10°C / min, a holding temperature of 400-600°C, and a holding time of 2-3h.
[0019] A highly active graphite felt for vanadium batteries is prepared by adopting the method for preparing the highly active graphite felt for vanadium batteries.
[0020] The beneficial effects of the present invention include at least:
[0021] The organic skeleton-metal oxide-organic skeleton structure prepared by the present invention is conducive to increasing the specific surface area and active sites of the graphite felt, thereby enhancing the activity of the graphite felt and further improving the electrochemical performance of the battery;
[0022] In the present invention, the molybdenum source is complexed with the organic phosphine source so that the molybdenum source can be exposed to the electrolyte, thereby enhancing the catalytic effect on the redox reaction of vanadium ions. At the same time, the complexation of the organic phosphine source can protect the molybdenum source from falling off or being consumed under the long-term catalytic reaction and the flushing of the electrolyte.
[0023] The organic sulfur source and organic phosphine source used in the present invention contain a large amount of P and S elements, and the doping of P and S elements can improve the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the graphite felt prepared in Example 6 of the present invention;
[0025] Figure 2 This is the XRD spectrum of the graphite felt prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0026] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1:
[0028] Step S1: 15 mL of thiophene and 100 mL of 1 mol / L dilute sulfuric acid were mixed as an electrolyte, graphite felt was used as a working electrode, a platinum sheet was used as an auxiliary electrode, and a silver chloride electrode was used as a reference electrode to polymerize the modified graphite felt using cyclic voltammetry, wherein the voltage window of the cyclic voltammetry was 0-1 V, the scan rate was 10 mV / s, and the number of cycles was 50;
[0029] Step S2: ammonium molybdate and deionized water are mixed to prepare a 5% ammonium molybdate solution, ammonia water is added to adjust the pH to 9, modified graphite felt is added, and then the solution is transferred to a hydrothermal reactor for hydrothermal treatment at 120° C. for 8 h;
[0030] Step S3: immersing the hydrothermally treated graphite felt in a phytic acid solution with a mass fraction of 10% for 8 hours to obtain a precursor graphite felt;
[0031] Step S4: heat-treating the precursor graphite felt in a nitrogen atmosphere at a heating rate of 2°C / min to 400°C for 2h to obtain highly active graphite felt.
[0032] Embodiment 2:
[0033] Step S1: 15 mL of 3-methylthiophene and 100 mL of 1 mol / L dilute sulfuric acid were mixed as an electrolyte, graphite felt was used as a working electrode, a platinum sheet was used as an auxiliary electrode, and a silver chloride electrode was used as a reference electrode to polymerize the modified graphite felt using cyclic voltammetry, wherein the voltage window of the cyclic voltammetry was 0-1 V, the scan rate was 10 mV / s, and the number of cycles was 50;
[0034] Step S2: Sodium molybdate and deionized water are mixed to prepare a sodium molybdate solution with a mass fraction of 10%, ammonia water is added to adjust the pH to 10, modified graphite felt is added, and then the solution is transferred to a hydrothermal reactor for hydrothermal treatment at 180° C. for 8 h;
[0035] Step S3: immersing the hydrothermally treated graphite felt in a 20% by mass aminotrimethylenephosphonic acid solution for 24 hours to obtain a precursor graphite felt;
[0036] Step S4: heat-treating the precursor graphite felt in a nitrogen atmosphere at a heating rate of 10°C / min to 600°C for 3 hours to obtain highly active graphite felt.
[0037] Embodiment 3:
[0038] Step S1: 15 mL of 3-chlorothiophene and 100 mL of 1 mol / L dilute sulfuric acid were mixed as an electrolyte, graphite felt was used as a working electrode, a platinum sheet was used as an auxiliary electrode, and a silver chloride electrode was used as a reference electrode to polymerize the modified graphite felt using cyclic voltammetry, wherein the voltage window of the cyclic voltammetry was 0-1 V, the scan rate was 10 mV / s, and the number of cycles was 50;
[0039] Step S2: molybdenum acetate and deionized water are mixed to prepare a molybdenum acetate solution with a mass fraction of 8%, ammonia water is added to adjust the pH to 9, modified graphite felt is added, and then the solution is transferred to a hydrothermal reactor for hydrothermal treatment at 160° C. for 8 h;
[0040] Step S3: immersing the hydrothermally treated graphite felt in a 15% by mass hydroxyethylidene diphosphonic acid solution to obtain a precursor graphite felt;
[0041] Step S4: heat-treating the precursor graphite felt in a nitrogen atmosphere at a heating rate of 5°C / min to 500°C for 2h to obtain highly active graphite felt.
[0042] Embodiment 4:
[0043] Step S1: 15 mL of 3-bromothiophene and 100 mL of 1 mol / L dilute sulfuric acid were mixed as an electrolyte, graphite felt was used as a working electrode, a platinum sheet was used as an auxiliary electrode, and a silver chloride electrode was used as a reference electrode to polymerize the modified graphite felt using cyclic voltammetry, wherein the voltage window of the cyclic voltammetry was 0-1 V, the scan rate was 10 mV / s, and the number of cycles was 50;
[0044] Step S2: ammonium molybdate and deionized water are mixed to prepare an ammonium molybdate solution with a mass fraction of 6%, ammonia water is added to adjust the pH to 9.5, modified graphite felt is added, and then the solution is transferred to a hydrothermal reactor for hydrothermal treatment at 150° C. for 8 h;
[0045] Step S3: immersing the hydrothermally treated graphite felt in a 12% by mass diethylenetriamine penta-methylenephosphonic acid solution to obtain a precursor graphite felt;
[0046] Step S4: heat-treating the precursor graphite felt in a nitrogen atmosphere at a heating rate of 2°C / min to 400°C for 3 hours to obtain highly active graphite felt.
[0047] Embodiment 5:
[0048] Step S1: 15 mL of 3-methylthiophene and 100 mL of 1 mol / L dilute sulfuric acid were mixed as an electrolyte, graphite felt was used as a working electrode, a platinum sheet was used as an auxiliary electrode, and a silver chloride electrode was used as a reference electrode to polymerize the modified graphite felt using cyclic voltammetry, wherein the voltage window of the cyclic voltammetry was 0-1 V, the scan rate was 10 mV / s, and the number of cycles was 50;
[0049] Step S2: ammonium molybdate and deionized water are mixed to prepare an ammonium molybdate solution with a mass fraction of 7%, ammonia water is added to adjust the pH to 9.8, modified graphite felt is added, and then the solution is transferred to a hydrothermal reactor for hydrothermal treatment at 150° C. for 8 h;
[0050] Step S3: immersing the hydrothermally treated graphite felt in a phytic acid solution having a mass fraction of 12% to obtain a precursor graphite felt;
[0051] Step S4: heat-treating the precursor graphite felt in a nitrogen atmosphere at a heating rate of 8°C / min to 600°C for 2h to obtain highly active graphite felt.
[0052] Embodiment 6:
[0053] Step S1: 15 mL of 3-bromothiophene and 100 mL of 1 mol / L dilute sulfuric acid were mixed as an electrolyte, graphite felt was used as a working electrode, a platinum sheet was used as an auxiliary electrode, and a silver chloride electrode was used as a reference electrode to polymerize the modified graphite felt using cyclic voltammetry, wherein the voltage window of the cyclic voltammetry was 0-1 V, the scan rate was 10 mV / s, and the number of cycles was 50;
[0054] Step S2: ammonium molybdate and deionized water are mixed to prepare an ammonium molybdate solution with a mass fraction of 8%, ammonia water is added to adjust the pH to 9, modified graphite felt is added, and then the solution is transferred to a hydrothermal reactor for hydrothermal treatment at 160° C. for 8 h;
[0055] Step S3: immersing the hydrothermally treated graphite felt in a phytic acid solution having a mass fraction of 15% to obtain a precursor graphite felt;
[0056] Step S4: heat-treating the precursor graphite felt in a nitrogen atmosphere at a heating rate of 5°C / min to 500°C for 3h to obtain a highly active graphite felt;
[0057] Figure 1 The scanning electron microscope image of the highly active graphite felt prepared in this embodiment clearly shows that the catalyst is loaded on the surface of the graphite felt fiber. Figure 2 The XRD spectrum of the highly active graphite felt prepared in this embodiment further shows that the highly active graphite felt fibers have obvious MoO 3 The characteristic peaks appear, indicating that MoO 3 Loaded on graphite felt fibers.
[0058] Comparative Example 1:
[0059] Blank graphite felt.
[0060] Comparative Example 2:
[0061] The preparation process is consistent with that of Example 6, except that no molybdenum source is involved in step S2, and no organic phosphine source is involved in step S3.
[0062] Comparative Example 3:
[0063] The preparation process is consistent with that of Example 1, except that no organic phosphine source is involved in step S3.
[0064] The graphite felts prepared in the embodiment and the comparative example were assembled into a stack, and a charge-discharge cycle test was performed under the same working conditions, and the coulomb efficiency, energy efficiency, voltage efficiency, and voltage efficiency after 100 cycles of the stack were recorded. The test results are shown in Table 1:
[0065] Table 1. Test results of graphite felt performance in examples and comparative examples
[0066]
[0067] The above test results show that compared with Comparative Example 1, Examples 1-6 have higher voltage efficiency and energy efficiency, indicating that the organic skeleton-metal oxide-organic skeleton structure prepared by the present invention is beneficial to increase the specific surface area and active sites of the graphite felt, so that the activity of the graphite felt is enhanced, thereby improving the electrochemical performance of the battery. At the same time, the organic sulfur source and the organic phosphine source used in the present invention contain a large amount of P and S elements, and the doping of P and S elements can further improve the electrochemical performance of the battery; Examples 1-6 have higher voltage efficiency and energy efficiency than Comparative Example 2, mainly because the molybdenum source of the present invention is complexed with the organic phosphine source, so that the molybdenum source can be exposed to the electrolyte and can effectively catalyze the vanadium ions, and the molybdenum oxide generated after pyrolysis has high catalytic activity; Compared with Comparative Example 3, Examples 1-6 have higher voltage efficiency and energy efficiency and the voltage efficiency is better maintained after 100 cycles, because the complexation of the organic phosphine source can protect the molybdenum source from falling off or being consumed under long-term catalytic reaction and electrolyte flushing.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing highly active graphite felt for vanadium batteries, characterized in that: The following steps are involved: Step S1: Mixing an organic sulfur source with dilute sulfuric acid as an electrolyte, using graphite felt as a working electrode, a platinum sheet as an auxiliary electrode, and a silver chloride electrode as a reference electrode to polymerize using cyclic voltammetry to obtain a modified graphite felt; the organic sulfur source is one of thiophene, 3-methylthiophene, 3-chlorothiophene, and 3-bromothiophene; the volume ratio of the organic sulfur source to the dilute sulfuric acid is 3:20; Step S2: mixing a molybdenum source and deionized water to obtain a molybdenum source solution, adding ammonia water to adjust the pH to 9-10, adding modified graphite felt, and then transferring to a hydrothermal kettle for hydrothermal treatment. After the end, taking out the graphite felt, washing and drying it to obtain a loaded graphite felt; Step S3: mixing an organic phosphine source and deionized water to obtain an organic phosphine source solution, and immersing the supported graphite felt in the organic phosphine source solution to obtain a precursor graphite felt; the organic phosphine source is one of phytic acid, aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and diethylenetriaminepentamethylenephosphonic acid, and the mass fraction of the organic phosphine source in the organic phosphine source solution is 10-20%; Step S4: heat-treating the precursor graphite felt in a nitrogen atmosphere to obtain highly active graphite felt.
2. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: The solubility of dilute sulfuric acid in step S1 is 1 mol / L.
3. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: The voltage window of the cyclic voltammetry in step S1 is 0-1 V, the scan rate is 10 mV / s, and the number of cycles is 50 times.
4. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: In step S2, the molybdenum source is one of sodium molybdate, ammonium molybdate and molybdenum acetate, and the mass fraction of the molybdenum source in the molybdenum source solution is 5-10%.
5. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: In step S2, the hydrothermal treatment temperature is 120-180° C. and the time is 8-24 hours.
6. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: The immersion time in step S3 is 8-24 hours.
7. The method for preparing a highly active graphite felt for vanadium batteries according to claim 1, characterized in that: The heat treatment conditions in step S4 are: heating rate of 2-10°C / min, holding temperature of 400-600°C, and holding time of 2-3h.
8. A highly active graphite felt for vanadium batteries, characterized in that: The highly active graphite felt is prepared by the method for preparing highly active graphite felt for vanadium batteries according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for obtaining N and P co-doped graphite felt electrode
CN116072891A
Energy storage device
US20130164602A1
Cited By
Multi-stage pore graphite felt for flow battery and preparation method of multi-stage pore graphite felt
CN121307052A
Gradient pulse electroplating catalytic electrode for iron-chromium flow battery as well as preparation method and application of gradient pulse electroplating catalytic electrode
CN121506976A
A gradient pulse electroplating catalytic electrode for iron-chromium liquid flow battery and a preparation method and application thereof
CN121506976B